In vitro algaecide effect of sodium hypochlorite and iodine based antiseptics on Prototheca zopfii strains isolated from bovine milk - Salerno, Tatiana [UNESP]; Ribeiro, Márcio Garcia [UNESP]; Langoni, Hélio [UNESP]; Siqueira, Amanda Keller [UNESP]; da Costa, Elizabeth Oliveira; Melville, Priscilla Anne; Felix Bueno, Valter Ferreira; Machado Yamamura, Aline Artioli; Roesler, Uwe; da Silva, Aristeu Vieira (Elsevier B.V., 2010)
Prototheca zopfii has been considered one of the most important causes of environmental mastitis in Brazil. These algae are refractory to conventional therapy and cause great damage to the mammary gland. The present study evaluated the in vitro algaecide effect of sodium hypochlorite and iodine based antiseptics on 27 P. zopfii strains isolated from the milk of cattle. Low concentrations of sodium hypochlorite (0.0390625-0.15625%) and iodine (0.15625-0.625%) were effective against the isolates. These antiseptics may be recommended for hygiene routines, pre and postdipping and cauterization of bovine mammary glands infected by P. zopfii. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Prototheca zopfii, antiseptics; Bovine mastitis; Milk; Brazil